(untitled) (مجلة الرازي الطبية, 2025)
Candida albicans threatens immunocompromised patients, partly via chlamydospores—dormant, stress-tolerant forms. Reducing these structures may limit persistence and relapse. We compared nystatin (polyenic membrane binder) versus ketoconazole (azole ergosterol-synthesis inhibitor) for suppressing chlamydospore production by C. albicans from cancer-patient oral lesions. Twenty isolates were cultured on cornmeal agar + 1% Tween-80 and exposed to nystatin or ketoconazole at 0.5–10 µg/mL. After 24–48 h at 30 °C, chlamydospores were stained and counted microscopically (spores/10 HPF). ANOVA with Tukey post-hoc tested drug, concentration, and interaction (p<0.05). Ketoconazole reduced chlamydospores more than nystatin at every concentration, with a clear dose response (≈54 to ≈29 spores/10 HPF from 0.5 to 10 µg/mL). Nystatin showed limited suppression at low doses and only modest declines at 5–10 µg/mL. At 10 µg/mL, ketoconazole achieved 45% reduction from baseline versus 30% with nystatin; 19/20 isolates favored ketoconazole. ANOVA showed significant main effects and drug-concentration interaction (p<0.001). Ketoconazole is superior to nystatin for suppressing C. albicans chlamydospore formation in vitro, supporting systemic azoles as more effective inhibitors of this persistence mechanism. Clinically, safer azoles (e.g., fluconazole) may better prevent recurrent or invasive disease in high-risk patients than topical nystatin alone. Nystatin remains useful for localized thrush but may not adequately block chlamydospore formation. In cancer patients with recurrent oral candidiasis or risk of dissemination, consider early systemic azole therapy and confirm in future studies whether aggressive chlamydospore suppression improves outcomes.